FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENGGUNAAN METODE KONTRASEPSI JANGKA PANJANG - Nuril Nikmawati (JURNAL KEBIDANAN, 2017)
The awareness about the importance of contraception in Indonesia still needs to be improved to prevent the increases in population. The use of LTCM an effective method of contraception helpful and efficient in the long term with less serious side effects. However, the use of LTCM in each year is less when compared to non LTCM.The study was conducted to analyze the factors associated with long-term use of contraceptive methods in the Northern District of Magelang This is an explanatory research with cross sectional approach. The study population is the mother of active family planning acceptors. The number of population is 3949 mother. Research Subjects 363 acceptors. Data was collected through interviews with a structured questionnaire and were analyzed by Chi-Square test and logistic regression. Results showed that mother who use LTCM as much as 51.8%. Results of univariate analysis age categories as much as 56.2%, secondary education as much as 51%, income above the MSE as much as 50.4%, the number of children as much as 69.7%. Most respondents have a poor knowledge (51.6%), have a negative perception (51.8%), had the support of health workers is less support (73.6%), husband support less (54.5%), and less attitude support (56.5%). Availability of tools (85.7%), largely at their own expense (68.6%). The results of the bivariate analysis of factors associated with the use of LTCM is earnings (p = 0.041) levels of knowledge (p = 0.002) attitude (p = 0.000) support of health workers (p = 0.037) availability of tools (p = 0.011) and the availability of funds (p = 0.002 ). Results of multivariate logistic regression (OR value = 4.157 and p = 0.000) in the acceptor attitude factor is the most influential factor on the use of LTCM. Acceptor attitude factor is the most influential factor on the use of LTCM Rated OR = 4.157, CI 95% of 2623 the lower limit and upper limit 6586.